Um partido contra a corrente: teses e disputas da Organização Revolucionária Marxista Política Operária (1961 – 1967) - Oliveira, Tiago Guimarães (2015)
This dissertation had as study object the thesis, programmatic formulations and the history of the Revolutionary Marxist Organization Workers Policy (1961-1967). The main thrust of these initial union militants Polop was the criticism of the position of the Communist Party of Brazil, the prospect of a socialist revolution in Brazil and are in favor of independence of the working class. The objective of this research was to analyze the paths taken by Polop in the formulation of their main theses and changes elapsed throughout its history, especially after the civil-military coup of 1964.